9 Importance of intrinsic cardiac nerves in both direct and remote ischaemic conditioning. (17th November 2015) - Pickard, JMJ; Davidson, SM; Yellon, DM
Abstract : Rationale: The intrinsic cardiac nervous system is important in our understanding of cardiac physiology. Using a pharmacological approach, we investigated the hypotheses that these nerves play a role in (1) direct ischaemic preconditioning (IPC) and (2) the cardioprotection offered by the humoral mediator of remote ischaemic conditioning (RIC). Methods: For the IPC experiment, isolated Langendorff perfused rat hearts were subjected to one of the following conditions; (1) Control + Hexamethonium (50 µM), (2) IPC (3 × 5-min global ischaemia) + Hexamethonium, (3) IPC alone. All hearts were subjected to 35-min ischaemia followed by 60-min reperfusion. In the second study, RIC (4 × 5 min hindlimb ischaemia/reperfusion) or sham was performed on anaesthetised rats, before exsanguination and centrifugation to obtain platelet-free plasma. After dialysis across a <12–14 kDa membrane, the dialysate was perfused through a naïve isolated Langendorff rat heart prior to an ischaemia-reperfusion injury, as described above. The hearts were assigned to the following groups; (1) Sham dialysate, (2) RIC dialysate, (3) Sham+hexamethonium (50 µM), (4) RIC+hexamethonium, (5) Sham+atropine (100 nM), (6) RIC+atropine (100 nM). All hearts were analysed for infarct size using triphenyl-tetrazolium chloride staining. Data presented as mean ± SEM and analysed using analysis of variance. Results: Hexamethonium partially, but significantly, abrogated IPC-mediated cardioprotection (Control = 44.4 ± 4.0%, IPC+Hex = 31.8 ± 5.0%, p < 0.05 vs IPC = 14.2 ± 1.9%). RIC dialysate significantly protected a naïve heart from injury (RIC = 27.6 ± 2.3 vs Control = 42.9 ± 1.2, p < 0.05). Both hexamethonium (45.8 ± 2.5%) and atropine (36.5 ± 3.4%) abrogated dialysate-mediated protection. Conclusion: Intrinsic cardiac nerves seem to be important in the induction of protection both in IPC and the response to the humoral RIC mediator.